The Application of Satellite Imagery Technology to Analyze the Effect of Land Use Changes on Runoff - boonma, raweewan; Charoenpanyanet, Arisara (Defence Technology Academic Journal, 2022)
A study on “Effects of land use change on runoff in the Upper Nan River Basin” had 2 objectives; 1) to analyze land use change with satellite data in the Upper Nan Basin and 2) to analyze effects of land use change on runoff in the Upper Nan Basin. Landsat-8 OLI data in 2016 and 2020 were use classification was carried out using supervised classification and analyzed land use change by analyzing the coefficients representing the magnitude of the correlation of the variables. Then SCS-CN model was performed to analyze amount of runoff. In this model, an annual rainfall data, land use types, soil types, and slope of the target area were applied. After that the result of land use change and runoff in two period was analyzed with statistical technique. The result found that between 2016 and 2020 forest area represents a decrease, but agricultural and urban areas represent an increase. And the results of the amount of runoff revealed that the average runoff in 2016 was 1,086.58 cubic meters per year and in 2020 was 1,534.00 cubic meters per year. The effect of land use change on runoff found that there is strong positive correlation with coefficient determination of 0.884.